We are given mid-point (-11, 18).
One end point (-5, 10).
[tex]\mathrm{Midpoint\:of\:}\left(x_1,\:y_1\right),\:\left(x_2,\:y_2\right):\quad \left(\frac{x_2+x_1}{2},\:\:\frac{y_2+y_1}{2}\right)[/tex]
Let us take coordinate of other end points is (x,y).
Therefore,
[tex]\left(x_1,\:y_1\right)=\left(-5,\:10\right),\:\left(x_2,\:y_2\right)=\left(x,\:y\right)[/tex]
[tex]\left(\frac{x_2+x_1}{2},\:\:\frac{y_2+y_1}{2}\right) =\left(\frac{x-5}{2},\:\frac{y+10}{2}\right)[/tex]
Given mid point (-11, 18).
Therefore,
[tex]\left(\frac{x-5}{2},\:\frac{y+10}{2}\right) = (-11, 18)[/tex]
[tex]\frac{x-5}{2}=-11[/tex] and [tex]\frac{y+10}{2} = 18[/tex]
Multiplying both sides by 2 in both equations, we get
x-5 = -22 and y+10 =36.
x = -22+5 and y = 36-10
x = -17 and y = 26.